EDUKASI DAN DEMONSTRASI CUCI TANGAN PAKAI SABUN (CTPS) SEBAGAI UPAYA PENCEGAHAN PENYAKIT INFEKSI PADA BALITA DI BALAIDESA PANEKAN, KABUPATEN MAGETAN - Lidia Deviga (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
The toddler period is a golden age as well as a vulnerable phase to various infectious diseases, such as diarrhea and Acute Respiratory Infections (ARI), which are frequently transmitted through unhygienic hands. This community service aims to increase knowledge and awareness of the importance of Clean and Healthy Living Behaviors (Perilaku Hidup Bersih dan Sehat / PHBS) through Education and Demonstration activities on Handwashing with Soap (Cuci Tangan Pakai Sabun / CTPS) for toddlers, accompanied by parents/health cadres, at the Panekan Village Hall, Panekan District, Magetan Regency in March 2026. The methods used included interactive lectures, educational video screenings, and a demonstration of the 6-step handwashing technique according to WHO standards. The results of the activity showed a significant increase in the participants' (toddlers and parents) understanding regarding crucial times and proper handwashing procedures. Through a recreational approach, toddlers were able to practice the handwashing steps enthusiastically. In conclusion, this activity is effective in instilling hygienic habits from an early age to reduce the risk of infectious diseases among toddlers in Panekan Village.